Experience of family members as a result of children's hospitalization at the Intensive Care Unit - Alves, Maria Virgínia Martins Faria Faddul [UNESP]; Cordeiro, Juliana Gonzaga; Luppi, Claudia Helena Bronzato [UNESP]; Nitsche, Maria José Trevisani [UNESP]; Olbrich, Sandra Regina Leite Rosa [UNESP] (My University, 2013)
Objective. To describe the experience of family members as a result of children’s hospitalization at the Intensive Care Unit (ICU). Methodology. Descriptive and cross-sectional study. A structured interview was held with 20 relatives of patients hospitalized at two clinics of the Botucatu Medical School at Universidade Estadual Paulista “Júlio de Mesquita Filho”. Information was collected between July and September 2010. Results. The main characteristics of the participating relatives were: 80% mothers of the children; 70% low education level and 70% married. Sixty percent of the children were hospitalized at the ICU for the first time. Eighty percent of the interviewees believe that the children’s behavior changes inside the unit and 85% consider that visiting hours are sufficient. The predominant negative feelings are fear (50%) and insecurity (20%), while the predominant positive feelings are hope (50%) and the expectation of discharge (25%). The professional who most supported the relatives was the nurse (35%). Conclusion. The family members’ experience as a result of the children’s hospitalization at the ICU involves positive and negative aspects, which also affect the child’s behavior at the unit.

Objetivo. Describir la experiencia vivida por los familiares con la internación de niños en la Unidad de Cuidados Intensivos (UCI). Metodología. Estudio descriptivo de tipo transversal. Se realizó una entrevista estructurada a 20 familiares de pacientes hospitalizados en dos clínicas de la Facultad de Medicina de Botucatu de la Universidade Estadual Paulista "Júlio de Mesquita Filho”. La información se recolectó entre julio y septiembre de 2010. Resultados. Las principales características de los familiares participantes fueron: 80%, madres de los niños; 70% tenía escolaridad baja y el 70% estaba casado. Fue la primera hospitalización en la UCI en el 60% de los niños. El 80% de los entrevistados cree que hay cambio en el comportamiento del niño dentro de la unidad y el 85% considera suficiente el tiempo de visita. Los sentimientos negativos predominantes son el miedo (50%) y la inseguridad (20%), mientras que los positivos son la esperanza (50%) y la expectativa del alta (25%). El profesional que más apoyo brindó al familiar fue el enfermero (35%). Conclusión. La experiencia de los familiares con la internación del niño en UCI tiene aspectos positivos y negativos, que incluso, afectan el comportamiento del niño en la unidad.

Objetivo. Descrever a experiência vivida pelos familiares com a internação de crianças na Unidade de Terapia Intensiva (UTI). Metodologia. Estudo descritivo de tipo transversal. Realizou-se uma entrevista estruturada a 20 familiares de pacientes hospitalizados em duas clínicas da Faculdade de Medicina de Botucatu da Universidade Estadual Paulista “Júlio de Mesquita Filho”. A informação se coletou entre julho e setembro de 2010. Resultados. As principais características dos familiares participantes foram: 80% eram mães das crianças, 70% tinham escolaridade baixa e o 70% estavam casados. Foi a primeira hospitalização na UTI em 60% das crianças. 80% dos entrevistados creem que há mudança no comportamento da criança dentro da unidade e 85% considera suficiente o tempo de visita. Os sentimentos negativos predominantes são o medo (50%) e a insegurança (20%), enquanto os positivos são a esperança (50%) e a expectativa do alta (25%). O profissional que mais apoio brindou ao familiar foi o enfermeiro (35%). Conclusão. A experiência dos familiares com a internação da criança na UTI tem aspectos positivos e negativos, que inclusive, afetam o comportamento da criança na unidade.
Experiencia vivida por los familiares con la internación de niños en la Unidad de Cuidado Intensivo
Experiência vivida pelos familiares com a internação de crianças na unidade de terapia intensiva
Keywords: Intensive care units; Pediatric; Family relations; Child; Unidades de cuidado intensivo pediátrico; Relaciones familiares; Niño; Unidades de terapia intensiva pediátrica; Relações familiares; Criança